A Comparative Study of Iran and Emerging Economies in Trajectories and Fundamental Indexes of Development: 1980-2020 - Seyed Rahim Teimouri (پژوهش‌های برنامه و توسعه, 2022)
One of the fundamental characteristics of development in the new era is the rise of emerging economies; So that the revival of China, India and Brazil, etc., will change the global geopolitical perspective. A look at the groupings and characteristics of emerging economies shows that these countries share one definition and that is that, along with economic growth and the struggle to keep pace in technology, they are heavily involved in trade and global markets. It is clear that Iran's transition to the status of an emerging economy, or rather, the country's current lack of success in upgrading to the rank of emerging economies, has its limits and differences, which the current study is trying to express comparatively. The current research is based on the fundamental proposition that the formation of emerging economies is based on the "last wave of globalization" in the 1980s and the expansion of capital in the "Global South". To demonstrate this proposition, four countries (China, India, Brazil, and Turkey) have been selected and compared with Iran in the context of qualitative comparative methods. The period of this study was chosen as 1980-2020, which coincides with the occurrence of the Islamic Revolution in Iran (as for the domestic dimension), and the occurrence of the last wave of globalization in the late 1970s and 1980s (as for the external dimension). The findings of the research show that due to the lack of comprehensive institutional reforms in Iran and the geopolitical and economic contractive conditions, especially in the last two decades, under nuclear tension sanctions, Iran is left behind from the new historical trajectory of emerging economies. Its obvious manifestation is the fluctuating, slow, and downward movement of the fundamental indicators of development in Iran compared to the model countries of this study.